BrRacemeCounter: Mask R-CNN for Raceme Instance Segmentation - International Center for Tropical Agriculture (CIAT) Tropical Forages Program; Arrechea-Castillo, Darwin Alexis; Cardoso Arango, Juan Andres (2024)
This is an adapted implementation of Mask R-CNN on Python 3, Keras, and TensorFlow. The model generates bounding boxes and segmentation masks for each instance of an object in the image. It's based on Feature Pyramid Network (FPN) and a ResNet50 or ResNet101 backbone.